Aspirin-induced attenuation of adipogenic differentiation of bone marrow mesenchymal stem cells is accompanied by the disturbed epigenetic modification. (May 2018) - Zhan, Yuanbo; He, Zhiwei; Liu, Xinpeng; Miao, Nan; Lin, Feng; Xu, Wenxia; Mu, Sen; Mu, Haibin; Yuan, Mengtong; Cao, Xiaofang; Jin, Han; Liu, Zhongshuang; et al.
Graphical abstract: Highlights Aspirin could induce inhibition of BMSCs adipogenic differentiation. Suppression of adipogenesis by aspirin is accompanied by alteration of epigenetic modification. HDAC9 has good affinity to aspirin and may play important role in the adipogenic inhibition caused by aspirin. Abstract: Aspirin has positive effects on bone marrow mesenchymal stem cells (BMSCs) osteogenic differentiation. However, researchers did not give much thought to its effect on BMSCs adipogenic differentiation. Here, we analyzed the effect of aspirin on the BMSCs adipogenic differentiation. To detect whether the effect of aspirin on the adipogenic differentiation of BMSCs is associated with the disturbed epigenetic modification, the expression of histone deacetylases (HDACs), activity of HDACs and HAT, global histone H3 acetylation and H3k9 acetylation alterations were investigated. Moreover, to further explore and understand the binding mode between aspirin and HDACs, an attempt was made to identify the interaction between aspirin and the HDACs with the aid of in silico docking study. The results showed that aspirin could induce inhibition of BMSCs adipogenesis. The level of HDAC activity, global histone H3 acetylation, and H3k9 acetylation were all down regulated during adipogenic differentiation, and aspirin can reverse these decreases. Furthermore, the HDAC isoforms have different expression patterns in those progresses. The expression of HDAC9 was increased in a does-dependent manner when aspirin was introduced during BMSCs adipogenic differentiation. Docking study showed that high affinity of HDAC9 to aspirin was existed, suggesting that HDAC9 may has an important role in the process of aspirin-induced suppression of adipogenesis. Further studies are needed to define the intricate mechanisms of the HDAC isoforms, and all of these enable us to understand aspirin and its efficacy of inhibition of adipogenic differentiation and pave the way to aspirin clinical using for the tissue regenerating.